Impact of salinity stress during reproductive stage on physiological responses and yield of landrace rice genotypes - Chorkaew Aninbon; Ruttanachira Ruttanaprasert; Wanwipa Pinta; Nattareeporn Rodnuch; Maythas Boonsom; Thanasin Thabthimtho; Nittaya Phakamas (BMC Plant Biology, 2026)
Salinity significantly reduces rice yield, particularly when stress occurs during the reproductive stage. This study aimed to evaluate the physiological and yield responses of rice genotypes subjected to salinity stress during this critical growth phase. The experiment followed a 4 × 10 factorial arrangements in a randomized complete block design (RCBD), comprising ten rice genotypes and four salinity levels (control, 6, 12, and 16 dS/m). Data were collected for electrolyte leakage, relative water content (RWC), proline content, SPAD chlorophyll meter reading (SCMR), total phenolic content, grain yield, and 1,000-seed weight. Salinity stress significantly affected both physiological and yield-related traits across all genotypes. Under 16 dS/m salinity, RWC and SCMR declined from 86.13% to 65.59% and from 41.86 to 26.56, respectively, at 14 days after salt application. Electrolyte leakage increased from 8.80% to 19.11% and from 13.12% to 33.23%, while proline accumulation rose sharply from 37.41 to 268.75 µg/g fresh weight. In contrast, total phenolic content decreased slightly from 7.22 to 6.38 mg/g dry weight. Among the genotypes, Met Makham produced the highest grain yield under control conditions (31.72 g/plant). Under moderate to severe salinity, however, Hom Yai consistently achieved the highest yields (18.35 and 15.14 g/plant at 12 and 16 dS/m, respectively) and exhibited the smallest yield reduction (42.12%) relative to the control at 16 dS/m. This reduction was lower than that observed in the salt-tolerant check variety Pokkali. Hom Yai also maintained high RWC (80.75%), SCMR (35.55), and phenolic content (7.22 mg/g), together with relatively low electrolyte leakage (20.91%) and stable yield performance under saline conditions. These findings suggest that Hom Yai was a promising genetic resource for cultivation in saline-prone areas and can serve as valuable parental lines in breeding programs aimed at developing high-yielding, salt-tolerant rice varieties.
Keywords: Plant Stress Responses and Tolerance; Rice Cultivation and Yield Improvement; Plant responses to water stress